Biomedical composites - Ambrosio, Luigi (Woodhead Publishing in materials., 2010)
Biocomposites are widely used in the medical industry to repair and restore bone, tooth, cartilage skin and other tissues. Biomedical composites, provides a thorough review of the current status, recent progress and future trends in composites for biomedical applications. Part one discusses the fundamentals of biocomposites with chapters on natural composites, design and fabrication of biocomposites, and hard and soft tissue applications of biocomposites. Part two then reviews applications of biocomposites. Chapters discuss composites for bone repair, composite coatings for implants, composites for spinal implants, injectable composites and composites for tissue engineered scaffolds. Chapters in part three discuss the biocompatibility, mechanical behaviour and failure of biocomposites with such topics as cellular response, testing of biocomposites and tribology of biocomposites. Finally part four reviews the future for biocomposites with chapters on nano-structured biocomposites, developing biocomposites as scaffolds and biocomposites in tissue engineering and regenerative medicine. With its distinguished editor and team of international contributors, Biomedical composites is an essential reference to materials scientists and researchers in industry and academia, as well as all those concerned with this increasingly important field. Provides a thorough review of the current status, recent progress and future trends in composites for biomedical applicationsDiscusses the fundamentals of biocomposites with chapters on natural composites, design and fabrication of biocomposites and their applicationsChapters address composites for bone repair, spinal implants and various other applications and discuss biocompatability, mechanical behaviour and failure of biocomposites.